Influence of anthropogenic activities on PAHs in sediments in a significant gulf of low-latitude developing regions, the Beibu Gulf, South China Sea: Distribution, sources, inventory and probability risk. Issue 1 (15th January 2015) - Li, Pingyang; Xue, Rui; Wang, Yinghui; Zhang, Ruijie; Zhang, Gan
Highlights: Current and history contaminations of 15 PAHs were performed in the Beibu Gulf. Three emission sources from industrialized urban areas and harbor were identified. Sediments here served as a significant sink of PAHs by the calculated mass inventory. Probability risk of PAHs in the surface sediments was assessed. PAHs in the sedimentary core were mainly from coal combustion. Abstract: Fifteen polycyclic aromatic hydrocarbons (PAHs) in 41 surface sediment samples and a sediment core (50 cm) from the Beibu Gulf, a significant low-latitude developing gulf, were analyzed. PAHs concentrations were 3.01–388 ng g − 1 (mean 95.5 ng g − 1 ) in the surface sediments and 10.5–87.1 ng g − 1 (average 41.1 ng g − 1 ) in the sediment core. Source apportionment indicated that PAHs were generated from coke production and vehicular emissions (39.4%), coal and biomass combustion (35.8%), and petrogenic sources (24.8%). PAHs were mainly concentrated in the industrialized and urbanized regions and the harbor, and were transported by atmospheric deposition to the marine matrix. The mass inventory (1.57–2.62 t) and probability risk showed sediments here served as an important reservoir but low PAH risk. Different from oil and natural gas in developed regions, coal combustion has always been a significant energy consumption pattern in this developing region for the past 30 years (56 ± 5%).